Goianiense choral literature on scene: a systematic review (Orfeu, 2024)
Extracted from ongoing doctoral research, this text aims to investigate, through a systematic review, works that address the choral literature of Goiás, and thereby identify the songs, which carry in their essence aspects of the place and which have a technical, historical and stylistic character from the State of Goiás. The results reveal few studies on the choral literature of Goiás, but they highlight the importance of choral singing for the cultural and historical identity of the state. Among nine works analyzed, only two cover original choir repertoires, both mentioning the composer Estércio Marquez Cunha: six of his compositions adhere to the research requirements, integrating local aspects of the Cerrado Goiano, as well as technical and historical aspects of Goiás. The other seven Studies mainly explore the historical perspective, using sources such as collections, chronicles and documents to address choral music in Goiás. However, this repertoire generally has a sacred character and written in Latin, not meeting the central question of the research. In general, research sees Goiani's choral literature as an expression of identity, a structured form of expression, an instrument of spiritual and human edification, a significant symbol, a way of approaching temporalities and spatialities. In this context, the present work, within the scope of performance studies, contributes to a more comprehensive understanding of choral music and its evolution over time in the local context.
Keywords: choral literature; choral singing; Goiania Goias; performance studies; cultural identity